Diversity and Bioactive Potential of Culturable Fungal Endophytes of Medicinal Shrub Berberis aristata DC.: A First Report. Issue 4 (2nd October 2018) - Sharma, Supriya; Gupta, Suruchi; Dhar, Manoj K.; Kaul, Sanjana
Abstract: Bioactive natural compounds, isolated from fungal endophytes, play a promising role in the search for novel drugs. They are an inspiring source for researchers due to their enormous structural diversity and complexity. During the present study fungal endophytes were isolated from a well-known medicinal shrub, Berberis aristata DC. and were explored for their antagonistic and antioxidant potential. B. aristata, an important medicinal shrub with remarkable pharmacological properties, is native to Northern Himalayan region. A total of 131 endophytic fungal isolates belonging to eighteen species and nine genera were obtained from three hundred and thirty surface sterilized segments of different tissues of B. aristata . The isolated fungi were classified on the basis of morphological and molecular analysis. Diversity and species richness was found to be higher in leaf tissues as compared to root and stem. Antibacterial activity demonstrated that the crude ethyl acetate extract of 80% isolates exhibited significant results against one or more bacterial pathogens. Ethyl acetate extract of Alternaria macrospora was found to have potential antibacterial activity. Significant antioxidant activity was also found in crude ethyl acetate extracts of Alternaria alternata and Aspergillus flavus . Similarly, antagonistic activity of the fungal endophytes revealed that all antagonists possessed inhibition potential against more than one fungal pathogen. This study is an important step towards tapping endophytic fungal diversity for bioactive metabolites which could be a step forward towards development of novel therapeutic agents.